A novel germline mutation of the PTENgene in a patient with macrocephaly, ventricular dilatation, and features of VATER association. Issue 12 (1st December 2001) - Reardon, William; Zhou, Xiao-Ping; Eng, Charis
Abstract : Mutations of the PTEN gene are associated with hamartoma-neoplasia syndromes. While germline mutations at this chromosome 10q22-23 locus have been observed in patients with Cowden syndrome (CS) and Bannayan-Riley-Ruvalcaba syndrome (BRR), both of which phenotypes are associated with hamartomata and neoplasia, somatic mutation of PTEN has been established in a wide variety of sporadically occurring neoplasia. CS and BRR share some clinical features, specifically hamartomata and lipomatosis. Investigation of other clinically distinct syndromes associated with lipomatosis and overgrowth has established germline and germline mosaic PTEN mutations in several patients with Proteus syndrome. To this expanding array of clinically distinct phenotypes associated with PTEN mutations, we now report a novel heterozygous germline mutation, H61D, in a patient with features of VATER association with macrocephaly and ventriculomegaly.